Television Truths - Hartley, John (2008)
Television Truths considers what we know about TV, whether we love it or hate it, where TV is going, and whether viewers should bother going along for the ride. This engaging volume, written by one of television's best known scholars, offers a new take on the history of television and an up-to-date analysis of its imaginative content and cultural uses. Explores the pervasive, persuasive, and powerful nature of television: among the most criticized phenomena of modern life, but still the most popular pastime ever Written by John Hartley, one of television's best known scholars Considers how television reflects and shapes contemporary life across the economic, political, social and cultural spectrum, examining its influence from historical, political and aesthetic perspectives Probes the nature of, and future for, television at a time of unprecedented change in technologies and business plans Provides an up-to-date analysis of content and cultural uses, from the television live event, to its global political influence, through to the concept of the "TV citizen" Maps out a new paradigm for understanding television, for its research and scholarship, and for the very future of the medium itself. © 2008 John Hartley.